Hubungan Asupan Zat Gizi Makro dengan Status Gizi Pasien Rawat Jalan Tuberkulosis Paru di RSUD Haji Provinsi Jawa Timur: The Correlation Between Macronutrient Intake and Nutritional Status Of Pulmonary Tuberculosis Outpatients At Haji Regional Hospital - Sellyardi Putri, Nathania Zabrina; Satwika Arya Pratama; Cleonara Yanuar Dini; Wildan Alfira Gusrianto (UNIVERSITAS NGUDI WALUYO, 2025)
Pulmonary tuberculosis patients have increase in Resting Energy Expenditure (REE) and metabolic disorders due to Mycobacterium tuberculosis infection, which tends to result in malnutrition. Macronutrients play an important role in providing energy to strengthen the immune system's ability to fight disease and improve the nutritional status of pulmonary tuberculosis patients. The study aimed to determine the correlation between macronutrient intake and the nutritional status of pulmonary tuberculosis outpatients at Haji Regional Hospital. This study was quantitative research with cross-sectional approach. The sampling technique used was purposive sampling, with 60 respondents. Macronutrients intake data were obtained through interviews using Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), while nutritional status data were obtained by measuring height using a stadiometer and weight using a mechanical column scale. The analysis results showed that majority of respondents had inadequate macronutrient intake, with 90% of patients had deficient carbohydrate intake, 91,7% had deficient protein intake, and 55% had deficient fat intake. While 31,7% patients were undernourished, 53,3% had normal nutritional status, and the rest were overweight or obese. Pearson test showed that there is a correlation between carbohydrate intake (p=0.007), protein intake (p=0.041), and fat intake (p=0.000) with nutritional status. It can be concluded that there is a significant correlation between macronutrient intake and nutritional status of pulmonary tuberculosis outpatients at Haji Regional Hospital. ABSTRAK Penderita tuberkulosis paru mengalami peningkatan Resting Energy Expenditure (REE) dan gangguan metabolisme tubuh akibat infeksi Mycobacterium tuberculosis, sehingga mereka cenderung memiliki status gizi kurang. Zat gizi makro memiliki peranan yang sangat penting dalam penyediaan energi, yang dapat memperkuat sistem kekebalan tubuh dalam melawan penyakit serta meningkatkan status gizi pada pasien tuberkulosis paru. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara asupan zat gizi makro dengan status gizi pasien rawat jalan tuberkulosis paru di RSUD Haji Provinsi Jawa Timur. Studi ini adalah penelitian kuantitatif yang menggunakan pendekatan cross-sectional. Metode pengambilan sampel yang diterapkan adalah purposive sampling dengan jumlah sampel yang diperoleh sebanyak 60 responden. Data asupan zat gizi makro diperoleh melalui wawancara Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), sedangkan data status gizi diperoleh dari pengukuran tinggi badan menggunakan stadiometer dan berat badan dengan menggunakan timbangan kolom mekanik. Hasil analisis menunjukkan asupan zat gizi makro sebagian besar responden termasuk kategori kurang, yakni sebanyak 90% pasien dengan asupan karbohidrat kurang, 91,75 pasien dengan asupan protein kurang, dan 55% pasien dengan asupan lemak kurang. Sementara itu, 31,7% pasien memiliki status gizi kurang, 53,3% pasien dengan status gizi normal, dan sisanya mengalami kelebihan berat badan atau obesitas. Hasil uji korelasi Pearson mengindikasikan adanya hubungan antara asupan karbohidrat (р=0,007), asupan protein (р=0,041), dan asupan lemak (р=0,000) dengan status gizi. Maka dari itu, dapat disimpulkan bahwa terdapat hubungan yang signifikan antara asupan zat gizi makro dengan status gizi pasien rawat jalan tuberkulosis paru di RSUD Haji Provinsi Jawa Timur.